TRANSFORMATIONAL LEADERSHIP, MOTIVATION TO LEARN, INNOVATIVE WORK BEHAVIOR, AND JOB PERFORMANCE: A LEADERSHIP BEHAVIORAL DEVELOPMENT - Ardi, Ardi; Meilani, Yohana F. Cahya Palupi; Tandiarak, Agustinus; Angelina, Inez (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This research explores leadership behavior development through the interaction of transformational leadership, motivation to learn, innovative work behavior, and employee performance. Previous research findings have shown a positive correlation between transformational leadership, motivation to learn, innovative work behavior, and increased employee performance. This research explores leadership behavior development through the abovementioned three factors. The data used in this research was collected from 75 employees working at PT XYZ in South Jakarta from September to December 2023. The statistical method uses Partial Least Square (PLS) Structural Equation Modeling (SEM) with bootstrapping analysis. Statistically, it is proven that transformational leadership significantly interacts with motivation to learn, innovative work behavior, and employee performance. Motivation to learn has a significant positive effect on innovative work behavior and employee performance, and innovative work behavior has a significant positive impact on employee performance. It was found that motivation to learn and innovative work behavior mediate between transformational leadership and employee performance. The research results suggest the importance of developing leadership attitudes through transformational leadership and motivating employees to continue learning to produce innovative ideas for the company's progress. Leaders recommend training and development programs that enhance transformational leadership, managerial leadership, and innovative work behavior for improved employee performance. Leaders facilitate effective communication and collaboration between relevant departments to foster a culture of innovation.